2010
DOI: 10.1007/s00415-010-5526-3
|View full text |Cite|
|
Sign up to set email alerts
|

Botulinum toxin type A in post-stroke lower limb spasticity: a multicenter, double-blind, placebo-controlled trial

Abstract: Lower limb spasticity in post-stroke patients can impair ambulation and reduces activities of daily living (ADL) performance of patients. Botulinum toxin type A (BoNTA) has been shown effective for upper limb spasticity. This study assesses the treatment of lower limb spasticity in a large placebo-controlled clinical trial. In this multicenter, randomized, double-blind, parallel-group, placebo-controlled study, we evaluate the efficacy and safety of one-time injections of botulinum toxin type A (BoNTA) in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
139
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 21 publications
8
139
0
5
Order By: Relevance
“…29,30 Ryuji Kaji et al 8 found that BoNT-A significantly reduced spasticity in the lower limb muscles in a study in which 120 patients with lower limb spasticity were randomized to a single treatment with 300 U BoNT-A or placebo. The application of Dysport (BoNT-A) in 74 patients reduced the degree of hip adductor spasticity associated with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29,30 Ryuji Kaji et al 8 found that BoNT-A significantly reduced spasticity in the lower limb muscles in a study in which 120 patients with lower limb spasticity were randomized to a single treatment with 300 U BoNT-A or placebo. The application of Dysport (BoNT-A) in 74 patients reduced the degree of hip adductor spasticity associated with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…31 Botulinum toxin type A alone was shown to be effective for reducing spasticity in several double-blind, placebocontrolled, randomized controlled trials. [8][9][10][11][12] Botulinum toxin type A was shown to be an effective treatment of painful localized contractures in RHT, even without central nervous system lesions. 32 Therefore, BoNT-A may be a useful option for painful localized contractures that do not respond to standard treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Botulinum toxin type A is derived from Clostridium botulinum; and when injected into a spastic muscle, it inhibits acetylcholine release, causing a blockade of the neuromuscular patches without affecting the antagonist muscles. 7 Botulinum toxin type A has been used in the past with mild improvements in conjunction with physiotherapeutic approaches. 8,9 However, to our knowledge, publication of this combination with manual therapy has not been reported.…”
Section: Introductionmentioning
confidence: 99%